Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1097/dad.0b013e31816797e4
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine Receptor Expression in Merkel Cell Carcinoma

Abstract: Neurocrest-derived tissues express muscarinic and nicotinic acetylcholine receptors (mAChR and nAChR respectively). These receptors are critical for migration of neurocrest-derived cells to their corresponding tissues during development. Recent reports demonstrate neurocrest-derived melanoma and numerous non-Merkel cell neuroendocrine tumors express both muscarinic and nicotinic receptors. In light of the controversy surrounding the origin and pathogenesis of Merkel cell carcinoma (MCC), we investigated the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…As shown in Table 1, muscarinic receptor expression is reported in tissues and cell lines derived from cancer of the brain (58) lung (114,115), ovary (93), pancreas (2,116), prostate (8,84), skin (15,16,108), stomach (76), and uterus (116). Nonetheless, because muscarinic receptor expression is common if not ubiquitous in all tissues, simply demonstrating expression of muscarinic receptors is insufficient to conclude that muscarinic signaling plays an important role in cancer progression.…”
Section: Proposed Criteria To Validate Muscarinic Receptor-mediated Amentioning
confidence: 92%
“…As shown in Table 1, muscarinic receptor expression is reported in tissues and cell lines derived from cancer of the brain (58) lung (114,115), ovary (93), pancreas (2,116), prostate (8,84), skin (15,16,108), stomach (76), and uterus (116). Nonetheless, because muscarinic receptor expression is common if not ubiquitous in all tissues, simply demonstrating expression of muscarinic receptors is insufficient to conclude that muscarinic signaling plays an important role in cancer progression.…”
Section: Proposed Criteria To Validate Muscarinic Receptor-mediated Amentioning
confidence: 92%
“…By immunohistochemistry, Bowers et al (2008) reported that 15 of 15 primary cutaneous cases of Merkel cell carcinoma expressed M3 and M5 receptors. Given that the proliferation of other types of neuroendocrine cells such as pulmonary neuroendocrine cells that express muscarinic receptors can be inhibited by M3 antagonists, this would suggest that muscarinic antagonists might also inhibit growth of Merkel Cell Carcinomas, but this again needs to be determined.…”
Section: Muscarinic Receptors and Specific Cancersmentioning
confidence: 99%
“…Although the roles of MRs in conferring malignancy to various tumour cells is a widely pursued hypothesis [6,7,8,26], in case of the skin the interpretation became somewhat difficult, as in the meantime the presence of all five MRs was described in healthy melanocytes and their functionality was also proven [4]. Recently the role of the nonneural cholinergic signalization in the physiological and pathological skin functions became widely accepted (see [5] and for recent reviews [27,28]).…”
Section: Muscarinic Acetylcholine Receptors Is Melanoma Cellsmentioning
confidence: 99%